Prevention of Administrative Torts in the Field of Using and Protecting Forestry Fund of Ukraine - Teremetskyi, Vladyslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The author of the article has studied administrative and legal provision for the prevention of administrative torts in the field of using and protecting forestry fund in Ukraine. The system of complex and special measures of crime prevention in the field of using and protecting forestry fund has been determined. The author has analyzed the practice of court hearings in regard to compensation of damage caused to the forest as a result of violations of the norms of forest legislation. Factors that contribute to the commission of offenses in this area have been identified.Particular attention has been focused on the insufficient degree of responsibility within administrative proceedings and the need to strengthen penalties in the Articles of the Code of Ukraine on Administrative Offenses, which determine the procedure for bringing to liability for administrative offenses in order to prevent criminal offenses while using forestry fund and causing significant damage to the environment in Ukraine.The author has substantiated the expediency of the development and adoption of the Law of Ukraine “On the Forestry Fund of Ukraine”, which would contain a separate Section on the prevention of offenses in the field of protecting and using forestry fund, which would define the areas of preventive activities and mechanism of applying legislation on state regulation of preventing administrative offenses in the sphere of using and protecting forestry fund of Ukraine.The author has formulated own definition of the concept of prevention of administrative offenses in the field of using and protecting forestry fund. The author has suggested to divide the measures aimed at identifying and eliminating the causes and conditions that contribute to the commission of illegal actions in this area into administrative (environmental audit, monitoring, scheduled and unscheduled inspections) and organizational (educational and outreach work, effective personnel policy, raids in order to identify and prevent violations of forest legislation). It has been concluded that the prevention of offenses in the field of using and protecting forestry fund performs protective, preventive and regulatory functions.